Comparison of Mathematics Learning Outcomes Between Students Taught Using Direct Teaching and Discovery Learning Models - Rahmayanti, Marina; Kwalat, Kevin Simon (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: To determine the differences in learning outcomes between students taught using the direct teaching model and students taught using the discovery learning model. Methodology: The research method used is quasi-experimental design. The population in this study were students of grade VII of State Junior High School 1 Wonomulyo and 2 classes were randomly selected as experimental classes for the study. The study was conducted by giving two different treatments to two groups of students. First, experimental class I received teaching using a direct teaching model, then experimental class II used a discovery learning model. Data collection was carried out by giving tests to students at the beginning and end of the study. Main Findings: The research results show that there is a significant difference in improving the learning outcomes of students taught using the direct teaching model with students taught using the discovery learning model. Novelty/Originality of this study: This study offers new insights into the effectiveness of direct instruction models compared to discovery learning in improving students' mathematics learning outcomes.